Happy feet: the key roles of podosomes and invadopodia in trophoblast invasion at the maternal-fetal interface - Murthi, Padma; Overton, Emily; Brennecke, Shaun P.; Keogh, Rosemary J. (Frontiers in Endocrinology, 2025)
Cells move by forming specialized projections or invasive feet known as podosomes in normal invasive cells and invadopodia in transformed and cancer cells. An understanding of invasive projections of trophoblasts at the maternal-fetal interface and their formation is important for developing novel therapies for pregnancy complications where invasion is abnormal, in instances where over- or under-invasion of cells manifests as serious pregnancy pathologies such as accreta or preeclampsia. Podosomes and invadopodia have distinctive morphological and molecular features that are used to distinguish them from each other. Despite this, there is still debate and uncertainty around how to definitively classify them. Analyses of novel models of cell invasion have demonstrated the existence of hybrid structures that are neither true podosomes nor invadopodia but which display features of both. This raises the question as to whether the classification of invasive structures needs redefining.